(untitled) (Journal of Plant Disease Sciences, 2020)
Enhancement of biocontrol efficiency of T. asperellum was carried out through chemical and physical mutagenesis and results revealed that significant differences within the T.asperellum mutants in comperesion to mother culture. Mutant TaH2 exhibited the highest antagonism ability against Sclerotium rolfsii with a percentage 88.89%. The next effective mutants were TaG2, TaH4 and TaG4exhibit 83.33, 77.78 and 75.00 % percent growth inhibition of Sclerotium rolfsii, respectively. Similarly, all the Trichoderma asperellum mutants were significant in inhibiting the radial mycelial growth of Rhizoctonia bataticola. The mutant TaH2contain highest i.e. 0.98 chitinase enzyme units/mg of protein to the tune of 47.15 to 75.38 % growth inhibition.in comparison to mother culture (control)contained only 0.62 chitinase enzyme units/ mg of protein.